PELAYANAN PEMERIKSAAN KESEHATAN, PENGOBATAN GRATIS, DAN SOSIALISASI PELATIHAN FISIK BAGI MASYARAKAT DI BANJAR CELUK DESA PANJER DENPASAR - Juhanna, Indira Vidiari (Buletin Udayana Mengabdi; Vol 19 No 4 (2020): Buletin Udayana Mengabdi, 2020)
ABSTRACT Health services is one of the important components in the national health development program, therefore it is necessary to improve the health status of Indonesian society, especially in Bali. An Analysis of the global, regional and national situation in 2030, non-communicable diseases, metabolic diseases is increasing compared to infectious diseases. Health services include general health examination, free medical treatment, and physical training on metabolic diseases socialization for the community in Banjar Celuk, Panjer, Denpasar. The result of this activity is some residents suffer from diseases due to aging such as lower back pain, knee pain and shoulder or neck pain, high blood pressure, high blood sugar levels, high cholesterol, and high uric acid. The conclusion is the community's enthusiasm and for this health examination service is very high.   Keywords: non communicable diseases, metabolic diseases, health examination, exercise training.